Demand for Labor in Industry - Fariha azzahra; Recita Permata Sari (JMBPreneur: Jurnal Manajemen, Bisnis, dan Kewirausahaan, 2022)
Background : The problem of labor is a very complex and big problem. Good working conditions, high output quality, decent wages and the quality of human resources are issues that always arise in discussions about the workforce in addition to issues of industrial relations between workers and the business world. It can be said that employment in Indonesia is still facing some structural and sectoral imbalances.Purpose: Determine targets that need to be pursued such as increasing the efficiency of the workforce. The demand for labor is affected by the marginal value of the product (Value of Marginal Product, VMP).Methods: The research method used is a literature survey and quantitative methods to define concepts and develop measurements.Conclusion: It can be said that the workforce in Indonesia is still facing a number of imbalances, both structural and sectoral. Even though there has been a shift, the majority of Indonesia's workforce is still working in the agricultural sector.suggestions : To realize the utilization of manpower, namely by various policies to expand productive employment. The main objective of the policy is to create conditions and atmosphere which not only provide the widest possible space for initiatives for economic actors but also at the same time encourage and assist the development of small businesses, businesses in the informal sector and traditional businesses. Theoretically, labor demand and wages must be considered so that the policies implemented are close to the desired goals